Adapting Public Space: The Case of Peripheral Urban Community Wellness - Svagzdiene, Biruta; Perkumiene, Dalia; Petraskaite, Urte; Simanavicius, Arturas (Transformations In Business & Economics, 2024)
The main idea developed in the article is that instead of trying to prove that a public space exists in Europe or, on the contrary, that a public space or public spaces have not yet been formed, we should look at Europe as a whole of multifaceted networks. These networks have many unique public spaces. The topic of regional differences in the adaptation of public spaces to health needs is indeed found in scientific works, but so far it has not been presented in the context of a peripheral region. This scientific article stands out from the others in that it aims to look at the adaptation of public spaces to the needs of wellness in the periphery in a broader way - in a complex way, by understanding and studying the influence zones of factors located in the city territory from the point of view of the residents themselves. The goal is to evaluate the adaptation of public space to the health of the peripheral city community. Maintaining physical activity is important for every person. One of the most important factors in maintaining a positive state of well-being is public space. Health and public space are inseparable. Green natural areas provide many psychological and physical benefits: they provide an opportunity to promote physical activity, actively spend your free time, and help improve your emotional state. From the point of view of residents, public spaces provide economic and social benefits to the city and its residents: active promotion of tourism in the city, which is very important for the economic and social growth of the city, health benefits, benefits for children’s development, promotes physical activity, all these factors are very important for every community and city psychological and physical well-being of the population.